Influence of abiotic elicitors on improvement production of artemisinin in cell culture of Artemisia annua L. - Zebarjadi, Alireza; Dianatkhah, Saeideh; Pour Mohammadi, Payam; Qaderi, Ardeshir (Cellular and Molecular Biology, 2018)
A significant sesquiterpene lactone used as a drug is artemisinin. It is definitely an anti-parasitic drug isolated from field-grown Artemisia annua L. a plant from Asteraceae family. It is the best treatment for Plasmodium falciparum malaria. Unfortunately, artemisinin content in A. annua is extremely low (0.01-0.8% dry weight). So, some researchers focused on enhancing artemisinin content either in tissue/cell culture or the whole plant of A. annua sp. The aims of the current study were the effect of plant growth regulators on callus production and improvement of artemisinin content in cell suspension culture of A. annua, an alternative to the whole plant using abiotic elicitors. For callus induction, an experiment was laid out as a factorial experiment with three factors (explant type, different concentrations of BAP and 2,4-D) based on completely randomized design with three replications. The maximum frequency of callus induction (100%) was found in leaf explant on MS medium with a combination of 2, 4-D (3 mg/l) and BAP (1.5 mg/l). Therefore, the best calli were used for cell suspension culture and the effects of GA3 and ABA as abiotic elicitors were evaluated on the improvement of artemisinin production. The results indicated that both ABA and GA3 increased artemisinin content (2.02 fold and 1.67 fold in comparison to control respectively) in cell suspension culture.